HUBUNGAN DUKUNGAN KELUARGA DENGAN KEBERHASILAN PENGOBATAN TB PARU DI POLIKLINIK PARU RSUD JOMBANG: HUBUNGAN DUKUNGAN KELUARGA DENGAN KEBERHASILAN PENGOBATAN TB PARU DI POLIKLINIK PARU RSUD JOMBANG - Happi, M; Santoso, Shelfi Dwi Retnani Putri; Wijaya, Arif; Prasetyo, Joko (WELL BEING, 2021)
Introdaction: Pulmonary TB is an infectious disease caused by the bacillus Mycobacterium tuberculosis. Transmission is through the air and the source of transmission is TB patients whose sputum contains TB germs. The success of treatment is the result (output) of treatment carried out by TB patients, consisting of complete recovery and treatment marked by a negative sputum examination result at the end of treatment. Family support is the attitude, action, and acceptance of sick sufferers. Objective: to determine the relationship between family support and the success of pulmonary TB treatment at the Jombang Hospital polyclinic. Design: using an analytical design using a cross-sectional approach. The number of respondents 30 using purposive sampling, purposive method and in accordance with the inclusion criteria. The measuring instrument used is a questionnaire that has been tested for validity and reliability. The analysis used is the univariate analysis of the frequency distribution and the bivariate Chi¬_Square test.Results: The results showed that 21 people declared good family support and recovered but the results of the Chi_Square test were H0 accepted which means that there is no relationship between family support and the success of pulmonary TB treatment with p-value = 0.021 (< 0.05). Conclusion: it is hoped that the family can provide support to patients with pulmonary TB for the success of their treatment.